Medication adherence and its effect on health-related quality of life in respiratory tract infection patients using the St. George’s Respiratory Questionnaire and the Medication Adherence Report Scale - Sanatkumar Bharamu Nyamagoud; Sai Phalguna Prakash Chitralu; Princy Domnic Dsouza; Chandrashekhar Mallikarjun Patil; Vinod Ashok Koujalagi; Agadi Hiremath Viswanatha Swamy (Monaldi Archives for Chest Disease)
Respiratory tract infections (RTIs) are common and pose significant health challenges, particularly in economically disadvantaged regions. Medication adherence is believed to influence patient quality of life (QoL), but the extent of this impact remains unclear. A cross-sectional study was conducted at Vivekananda General Hospital, Hubballi, India, from August 2023 to January 2024 to assess the relationship between medication adherence and QoL in RTI patients. This study involved 200 patients from the pulmonology department. Medication adherence was evaluated using the Medication Adherence Report Scale, while QoL was assessed with the St. George’s Respiratory Questionnaire (SGRQ). A two-way analysis of variance was performed to examine associations between adherence and QoL scores. No significant correlation was found between medication adherence and QoL. SGRQ total, symptoms, activity, and impact scores did not differ significantly between less adherent and highly adherent patients (p: 0.570-0.944). Medication adherence alone may not significantly affect QoL in RTI patients. Other factors, including disease severity, medication efficacy, comorbidities, and socioeconomic conditions, might have a greater influence. Further research is needed to explore these determinants and develop strategies to improve patient outcomes.